High-capacity chlorinated hydrocarbon adsorbent as well as preparation method and application thereof
By using Fe/Cu metal organic framework materials (MOFs) as chlorinated hydrocarbon adsorbents and utilizing the coupling effect of bimetallic ions, the problem of incomplete removal of chlorinated hydrocarbons in the existing flue gas treatment process has been solved, achieving efficient and economical results. Excellent chlorinated hydrocarbon adsorption effect to meet strict emission standards.
Patent Information
- Application Number
- CN202411516653.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-29
AI Technical Summary
In the existing flue gas treatment processes, condensation method and membrane separation method are difficult to effectively remove chlorinated hydrocarbons, resulting in high residual amount of chlorinated hydrocarbons in the tail gas and cannot meet strict emission standards.
The FE/CU metal organic framework material (MOFS) is used as a high-volume chlorine hydrocarbon adsorbent, and the FEXCUY-MOFS adsorbent is synthesized through the water thermal method to enhance the adsorption capacity of chlorine hydrocarbons with the coupling of bipolar ions.
It significantly increases the adsorption capacity of chlorine hydrocarbons, meets the requirements of national emissions standards, while reducing the amount of adsorbent and the volume of the equipment, and reducing production costs.
Smart Images

Figure CN119346079A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flue gas treatment, and in particular to a high-capacity chlorinated hydrocarbon adsorbent and a preparation method and application thereof. Background Art
[0002] The tail gas from the production process of products such as dimethyl phosphite, silicone, glyphosate, chloromethane and vinyl chloride mainly contains chlorinated hydrocarbons. For example, the current treatment process for chloromethane tail gas is to purify it and then compress, condense and separate it through membrane to recover as much as possible. The condensation method is limited by vapor pressure. The vapor pressure of chlorinated hydrocarbons in the gas phase after condensation is the lowest partial pressure in the gas phase. For example, the vapor pressure of chloromethane at -23.64°C is 0.101MPa. Even at a pressure of 0.8MPa, the content in the gas phase is still higher than 12%; the driving force of membrane separation is the concentration difference. The treated membrane separation tail gas still contains 5% to 10% of chlorinated hydrocarbons. The content of chlorinated hydrocarbons in the tail gas after treatment by these two methods is much higher than the national emission standard GB 39727-20 "Air Pollutant Emission Standard for Pesticide Manufacturing Industry", which stipulates that the total organic matter emission requirement is less than 150mg / Nm 3 , and with the increasingly stringent environmental protection policies, the emission requirements in some areas are lower than 50mg / Nm 3 Therefore, the current industrial condensation method and membrane separation method cannot meet the accuracy requirements for removing chlorinated hydrocarbons from production tail gas.
[0003] Invention patents with publication numbers CN101012146A, CN103170214A and CN106966857A disclose the use of pressure swing adsorption process to adsorb methyl chloride with adsorbents, but none of them disclose the adsorption capacity of the adsorbents and whether the residual methyl chloride content in the tail gas meets the standard. The prior art also discloses the adsorption of methyl chloride by metal organic framework material MIL G53. The adsorption capacity of the adsorbent for CH2Cl2 is 16.88mmoL / g, and the adsorption capacity for CHCl3 is 7.11mmoL / g. Its adsorption capacity is relatively low. Under the premise of the same tail gas treatment volume, the required adsorbent volume is large and the cost is high. To solve this problem, a high-capacity adsorbent is needed, and the residual amount of chlorohydrocarbons in the tail gas is small after adsorbing the chlorohydrocarbons. Summary of the invention
[0004] In view of this, the present invention proposes a high-capacity chlorinated hydrocarbon adsorbent and a preparation method and application thereof. The adsorbent has a high adsorption capacity and a small amount of residual chlorinated hydrocarbons after adsorbing the chlorinated hydrocarbons in the tail gas.
[0005] The technical solution of the present invention is implemented as follows: In the first aspect, the present invention provides a high-capacity chlorinated hydrocarbon adsorbent, the structural formula of the adsorbent is Fe x Cu y-MOFs, the atomic ratio x:y of Fe / Cu is 1:4-19.
[0006] In a second aspect, the present invention provides a method for preparing a high-capacity chlorinated hydrocarbon adsorbent, comprising the following steps:
[0007] S1, using soluble iron salt and copper salt as raw materials, trimesic acid as organic ligand, adding organic-inorganic mixed solvent, and synthesized by hydrothermal method;
[0008] S2, after the reaction is completed, washing with an organic-inorganic mixed solvent and then drying to obtain an adsorbent.
[0009] On the basis of the above technical solution, preferably, the soluble iron salt is FeCl3·6H2O or Fe(NO3)3·9H2O, and the soluble copper salt is Cu(NO3)2·6H2O.
[0010] On the basis of the above technical solution, preferably, the molar ratio of the iron salt to the copper salt is 1:4-19.
[0011] On the basis of the above technical solution, preferably, the molar ratio of trimesic acid to the total amount of soluble iron salt and copper salt is 2:2-3.
[0012] On the basis of the above technical solution, preferably, the organic-inorganic mixed solvent is N,N-dimethylformamide, water and ethanol.
[0013] On the basis of the above technical solution, preferably, the volume ratio of N,N-dimethylformamide: water: ethanol is (0.5-2): (0.5-2): (0.5-2).
[0014] Based on the above technical solution, preferably, the hydrothermal reaction temperature is 80-110°C and the reaction time is 20-24h.
[0015] In a third aspect, the present invention provides the use of an adsorbent in adsorbing chlorinated hydrocarbons in tail gas.
[0016] On the basis of the above technical solution, preferably, the chlorinated hydrocarbons are methyl chloride, dichloromethane, chloroform and vinyl chloride.
[0017] The high-capacity chlorinated hydrocarbon adsorbent and its preparation method and application of the present invention have the following beneficial effects compared with the prior art:
[0018] (1) The acidity of the bimetallic ions is that the iron ions have a single electron orbit, which enhances the physical attraction of the chlorine atoms. The copper ions can be partially reduced to obtain some cuprous ions when used. The presence of some cuprous ions, coupled with the iron ions, significantly enhances the physical attraction of the chlorine atoms. 3+ and Cu 2+ ) makes the acidity of the adsorbent moderate, enhancing the attraction of chloride ions in chlorinated hydrocarbons, thereby increasing the adsorption capacity for chlorinated hydrocarbons.
[0019] (2) The adsorbent of the present invention has an adsorption capacity of 102.36 mmoL / g for CH3Cl, 36.43 mmoL / g for CH2Cl2, 15.16 mmoL / g for CHCl3, and 10.68 mmoL / g for vinyl chloride, which greatly improves the adsorption capacity and has high industrial application value.
[0020] (3) The adsorbent of the present invention can achieve an adsorption residual amount that meets emission requirements and meets emission standards; at the same time, under the condition of the same total amount of adsorption required, the amount of adsorbent used can be reduced, thereby reducing the volume of the equipment for loading the adsorbent, that is, the volume of the adsorption tower used, and further reducing the floor space required by industrial application equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 Infrared spectrum of the adsorbent. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] The high capacity chlorinated hydrocarbon adsorbent Fe of this embodiment 0.05 Cu 0.95 -The preparation method of MOFs comprises the following steps:
[0026] 0.1407g (0.67mmoL) of organic ligand trimesic acid (H3BTC) was dissolved in a solution of DMF 10mL + H2O 10mL + C2H5OH 10mL with a total volume of 30mL, and the solution was dissolved evenly by ultrasonication for 30min; 0.0135g (0.05mmoL) of FeCl3·6H2O and 0.2295g (0.95mmoL) of Cu(NO3)·6H2O were weighed into the above solution, and stirred at room temperature for 1h until the solution was clarified; the obtained solution was transferred to a polytetrafluoroethylene high-pressure reactor, the reactor was sealed, and placed in an oven at 110°C for reaction for 24h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85°C overnight to finally obtain HKUST-1 (5% Fe), i.e., Fe 0.05 Cu 0.95 -MOFs adsorbent.
[0027] Example 2
[0028] The high capacity chlorinated hydrocarbon adsorbent Fe of this embodiment 0.1 Cu 0.9 -The preparation method of MOFs comprises the following steps:
[0029] 0.1407g (0.67mmoL) of organic ligand trimesic acid (H3BTC) was dissolved in a solution of DMF 10mL + H2O 10mL + C2H5OH 10mL with a total volume of 30mL, and the solution was dissolved evenly by ultrasonication for 30min; 0.027g (0.1mmoL) of FeCl3·6H2O and 0.2174g (0.9mmoL) of Cu(NO3)·6H2O were weighed into the above solution, and stirred at room temperature for 1h until the solution was clarified; the obtained solution was transferred to a polytetrafluoroethylene high-pressure reactor, the reactor was sealed, and placed in an oven at 110°C for reaction for 24h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85°C overnight to finally obtain HKUST-1 (10% Fe), i.e., Fe 0.1 Cu 0.9 -MOFs adsorbent.
[0030] Example 3
[0031] The high capacity chlorinated hydrocarbon adsorbent Fe of this embodiment 0.2 Cu 0.8 -The preparation method of MOFs comprises the following steps:
[0032] 0.1407g (0.67mmoL) of organic ligand trimesic acid (H3BTC) was dissolved in a solution of DMF 10mL + H2O 10mL + C2H5OH 10mL with a total volume of 30mL, and the solution was dissolved evenly by ultrasonication for 30min. Then 0.054g (0.2mmoL) of FeCl3·6H2O and 0.1932g (0.8mmoL) of Cu(NO3)·6H2O were weighed into the above solution, and stirred at room temperature for 1h until the solution was clarified. The obtained solution was then transferred to a polytetrafluoroethylene high-pressure reactor, the reactor was sealed, and placed in an oven at 110°C for reaction for 24h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85°C overnight to finally obtain HKUST-1 (20% Fe), i.e., Fe 0.2 Cu 0.8 -MOFs adsorbent.
[0033] Example 4
[0034] The high capacity chlorinated hydrocarbon adsorbent Fe of this embodiment 0.1 Cu 0.9 -The preparation method of MOFs comprises the following steps:
[0035] 0.2102g (1mmoL) of organic ligand trimesic acid (H3BTC) was dissolved in a solution of DMF 3.75mL + H2O 11.25mL + C2H5OH 15mL with a total volume of 30mL, and the solution was dissolved evenly by ultrasonication for 30min. Then 0.0404g (0.1mmoL) of Fe(NO3)3·9H2O and 0.2174g (0.9mmoL) of Cu(NO3)·6H2O were weighed into the above solution, and stirred at room temperature for 1h until the solution was clarified. The obtained solution was then transferred to a polytetrafluoroethylene high-pressure reactor to remove the ions. After the reactor was sealed, it was placed in an oven at 80℃ for reaction for 22h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85℃ overnight to finally obtain HKUST-1 (10% Fe), i.e., Fe 0.1 Cu 0.9 -MOFs adsorbent.
[0036] Example 5
[0037] The high capacity chlorinated hydrocarbon adsorbent Fe of this embodiment 0.1 Cu 0.9 -The preparation method of MOFs comprises the following steps:
[0038] 0.1681g (0.8mmoL) of organic ligand trimesic acid (H3BTC) was dissolved in a solution of DMF 11.25mL + H2O 15mL + C2H5OH 3.75mL with a total volume of 30mL, and the solution was dissolved evenly by ultrasonication for 30min; 0.0404g (0.1mmoL) of Fe(NO3)3·9H2O and 0.2174g (0.9mmoL) of Cu(NO3)·6H2O were weighed into the above solution, and stirred at room temperature for 1h until the solution was clarified; the obtained solution was transferred to a polytetrafluoroethylene high-pressure reactor, the reactor was sealed, and placed in an oven at 100℃ for reaction for 20h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85℃ overnight to finally obtain HKUST-1 (10% Fe), i.e., Fe 0.1 Cu 0.9 -MOFs adsorbent.
[0039] Comparative Example 1
[0040] The preparation method of the chlorinated hydrocarbon adsorbent of Comparative Example 1 comprises the following steps:
[0041] 0.1407 g (0.67 mmol) of organic ligand H3BTC was dissolved in a solution of DMF 10 ml + H2O 10 ml + C2H5OH 10 ml with a total volume of 30 mL, and the solution was dissolved evenly by ultrasonication for 30 min. Then 0.2416 g (1 mmol) of Cu(NO3)·6H2O was weighed into the above solution and stirred at room temperature for 1 h until the solution was clarified. The obtained solution was then transferred to a polytetrafluoroethylene high-pressure reactor to remove the ions. After the reactor was sealed, it was placed in an oven at 110°C for reaction for 24 h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85°C overnight to finally obtain HKUST-1.
[0042] Comparative Example 2
[0043] The preparation method of the chlorinated hydrocarbon adsorbent of Comparative Example 2 comprises the following steps:
[0044] 0.1407g (0.67mmoL) of organic ligand H3BTC was dissolved in a solution of DMF 10ml+H2O 10ml+C2H5OH 10ml with a total volume of 30mL, and the solution was dissolved evenly by ultrasonication for 30min; 0.2702g (1mmoL) of FeCl3·6H2O was weighed into the above solution, and stirred at room temperature for 1h until the solution was clarified; the obtained solution was transferred to a polytetrafluoroethylene high-pressure reactor, the reactor was sealed, and placed in an oven at 110°C for reaction for 24h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85°C overnight to finally obtain MIL-100 (Fe).
[0045] Comparative Example 3
[0046] Comparative Example 3 Compared with Example 2 (HKUST-1 (25% Fe)), the molar ratio of iron salt to copper salt is 1:3. The specific method is:
[0047] 0.1407g (0.67mmoL) of organic ligand trimesic acid (H3BTC) was dissolved in a solution of DMF 10mL + H2O 10mL + C2H5OH 10mL with a total volume of 30mL, and the solution was dissolved evenly by ultrasonication for 30min. Then 0.06758g (0.25mmoL) of FeCl3·6H2O and 0.1813g (0.75mmoL) of Cu(NO3)·6H2O were weighed into the above solution, and stirred at room temperature for 1h until the solution was clarified. The obtained solution was then transferred to a polytetrafluoroethylene high-pressure reactor, the reactor was sealed, and placed in an oven at 110°C for reaction for 24h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85°C overnight to finally obtain HKUST-1 (25% Fe), i.e., Fe 0.25 Cu 0.75 -MOFs adsorbent.
[0048] Comparative Example 4
[0049] Comparative Example 4 Compared with Example 2 (HKUST-1 (4% Fe)), the molar ratio of iron salt to copper salt is 1:24. The specific method is:
[0050] 0.1407g (0.67mmoL) of organic ligand trimesic acid (H3BTC) was dissolved in a solution of DMF 10mL + H2O 10mL + C2H5OH 10mL with a total volume of 30mL, and the solution was dissolved evenly by ultrasonication for 30min; 0.0108g (0.04mmoL) of FeCl3·6H2O and 0.2310g (0.96mmoL) of Cu(NO3)·6H2O were weighed into the above solution, and stirred at room temperature for 1h until the solution was clarified; the obtained solution was transferred to a polytetrafluoroethylene high-pressure reactor, the reactor was sealed, and placed in an oven at 110°C for reaction for 24h and then cooled. The obtained product was exchanged and washed three times with DMF, water and ethanol respectively, and dried at 85°C overnight to finally obtain HKUST-1 (4% Fe), i.e., Fe 0.04 Cu 0.96 -MOFs adsorbent.
[0051] Comparative Example 5
[0052] Compared with Example 2 (HKUST-1 (10% Fe)), the oven temperature of Comparative Example 5 exceeds the specified range, specifically 120° C. for reaction for 24 h, and the rest of the contents are the same.
[0053] Comparative Example 6
[0054] Compared with Example 2 (HKUST-1 (10% Fe)), the reaction time of Comparative Example 6 exceeds the specified range, specifically, the reaction time is 26 h at 110°C.
[0055] from Figure 1 From the comparison of the absorption peaks, it can be seen that the relevant groups of the absorbents of Examples 1-3 of the present invention are successfully connected to the metal ions, making the acidity of the metal ions moderate and improving the adsorption capacity of the adsorbent for chlorinated hydrocarbons.
[0056] The adsorption capacity of the adsorbent is tested by filling the adsorbent in the adsorption tower, distributing the adsorbent bed evenly, passing the gas containing 20% chlorinated hydrocarbons into the adsorption tower from one end, passing through the adsorbent bed, and the adsorbed tail gas is discharged from the other end. When the chlorinated hydrocarbon content in the tail gas exceeds 50mg / Nm 3 , the experiment was stopped and the content of chlorinated hydrocarbons adsorbed by the adsorbent was detected. Adsorption conditions: adsorption pressure 0.5-0.8MPa, adsorption temperature 25℃. The results are shown in Table 1.
[0057] Table 1 Comparison of adsorption capacity of the adsorbents of the embodiments and comparative examples
[0058]
[0059]
[0060] As shown in Table 1, the adsorbent prepared by the present invention has a high adsorption capacity for chlorinated hydrocarbons, among which the adsorbent of Example 2 has the best effect, with an adsorption capacity of 102.36 mmoL / g for CH3Cl, 36.43 mmoL / g for CH2Cl2, 15.16 mmoL / g for CHCl3, and 10.68 mmoL / g for vinyl chloride, which has a high industrial application value. Reducing (Example 1) or increasing (Example 3) the iron content will reduce the adsorption capacity for chlorinated hydrocarbons. The adsorbent prepared by a single copper salt (Comparative Example 1) or iron salt (Comparative Example 2) has a significantly weakened attraction to chlorine atoms.
[0061] Comparative Examples 3-4 show that when the molar ratio of iron salt to copper salt exceeds the specified range of 1:4-19, the coupling effect of the two ions is weakened, the ability to attract chlorine atoms decreases, and the adsorption capacity for different types of chlorinated hydrocarbons is significantly reduced.
[0062] The hydrothermal reaction temperature is 80-110°C. The appropriate reaction temperature promotes the coordination reaction. If the temperature is too low, the reaction cannot proceed. If the temperature is too high, the structure of the organic ligand H3BTC will decompose, resulting in a significant decrease in the adsorption capacity. For example, in Comparative Example 5, the hydrothermal reaction temperature is 120°C, and no adsorption material is synthesized due to the structural decomposition of H3BTC.
[0063] During the hydrothermal reaction, if the reaction time is too short, the coordination reaction is not sufficient, and if the time is too long, the specific surface area of the obtained adsorbent is reduced, affecting the adsorption capacity of chlorinated hydrocarbons. The reaction time of Comparative Example 6 is too long, and after the adsorption of chloromethane is completed, the adsorption capacity is relatively low. Since it is an adsorbent for industrial application, it does not meet the adsorption requirements, and the subsequent adsorption of CH2Cl2, CHCl3 and CH2CHCl is not done.
[0064] Table 2 Tail gas emission data of the industrial pilot of the adsorbent HKUST-1 (10% Fe) of the present invention
[0065]
[0066] The adsorbent of the present invention is used in a pressure swing adsorption process. From the operating results of an industrial pilot, it can be seen that under the condition that the content of chlorinated hydrocarbons in the raw gas is between 20% and 25%, after three months of continuous and stable operation, the adsorbent has a good purification effect on chlorinated hydrocarbon tail gas, and the tail gas emissions are better than the national emission standards, and has significant industrial application value.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-capacity chlorinated hydrocarbon adsorbent, characterized in that: The structural formula of the adsorbent is Fe x Cu y -MOFs, the atomic ratio x:y of Fe / Cu is 1:4-19.
2. The method for preparing a high-capacity chlorinated hydrocarbon adsorbent as claimed in claim 1, characterized in that: The following steps are involved: S1, using soluble iron salt and copper salt as raw materials, trimesic acid as organic ligand, adding organic-inorganic mixed solvent, and synthesized by hydrothermal method; S2, after the reaction is completed, washing with an organic-inorganic mixed solvent and then drying to obtain an adsorbent.
3. The method for preparing a high-capacity chlorinated hydrocarbon adsorbent as claimed in claim 2, characterized in that: The soluble iron salt is FeCl3·6H2O or Fe(NO3)3·9H2O, and the soluble copper salt is Cu(NO3)2·6H2O.
4. The method for preparing a high-capacity chlorinated hydrocarbon adsorbent as claimed in claim 3, characterized in that: The molar ratio of the iron salt to the copper salt is 1:4-19.
5. The method for preparing a high-capacity chlorinated hydrocarbon adsorbent as claimed in claim 3, characterized in that: The molar ratio of the trimesic acid to the total amount of soluble iron salt and copper salt is 2:2-3.
6. The method for preparing a high-capacity chlorinated hydrocarbon adsorbent as claimed in claim 2, characterized in that: The organic-inorganic mixed solvent is N,N-dimethylformamide, water and ethanol.
7. The method for preparing a high-capacity chlorinated hydrocarbon adsorbent as claimed in claim 6, characterized in that: The volume ratio of the N,N-dimethylformamide: water: ethanol is (0.5-2): (0.5-2): (0.5-2).
8. The method for preparing a high-capacity chlorinated hydrocarbon adsorbent according to claim 1, characterized in that: The hydrothermal reaction temperature is 80-110°C and the reaction time is 20-24h.
9. Use of the high-capacity chlorinated hydrocarbon adsorbent as claimed in claim 1 in adsorbing chlorinated hydrocarbons in tail gas.
10. The use according to claim 9, characterized in that: The chlorinated hydrocarbons are methyl chloride, dichloromethane, chloroform and vinyl chloride.
Citation Information
Patent Citations
Metal-organic framework composite material with multiple active adsorption sites and preparation and application thereof
CN109647343A
Composite adsorbent for purifying VOCs in reagent cabinet and preparation method of composite adsorbent
CN113351170A
Preparation method and application of water-resistant MOFs-based material
CN114146688A
Bimetal FexCu-BTC photocatalytic material as well as preparation method and application thereof
CN118745253A
Metal organic frameworks as catalysts and hydrocarbon oxidation methods thereof
US20170326536A1